Development and validation of the Patient‐Physician Relationship Scale among patients with irritable bowel syndrome. Issue 10 (22nd May 2017) - Kurlander, J. E.; Chey, W. D.; Morris, C. B.; Hu, Y. J. B.; Padival, R. K.; Bangdiwala, S. I.; Norton, N. J.; Norton, W. F.; Drossman, D. A.
Abstract: Background: An effective patient‐physician relationship (PPR) is essential to the care of patients with irritable bowel syndrome (IBS). We sought to develop and validate an IBS‐specific instrument to measure expectations of the PPR. Methods: We conducted structured focus groups about PPRs with 12 patients with IBS. Qualitative analysis was used to generate a questionnaire (the Patient‐Physician Relationship Scale [PPRS]), which was modified with input from content experts and usability testing. For validation, we administered it online to US adults with IBS. Participants also completed the Functional Bowel Disorder Severity Index, the Rome III Adult Functional gastrointestinal (GI) Disorder Criteria Questionnaire, and modified versions of the Communication Assessment Tool (CAT‐15) and Patient‐Doctor Relationship Questionnaire (PDRQ‐9). We performed principal components factor analysis for the PPRS. Key Results: The PPRS contained 32 questions with responses on a 7‐item Likert scale. Themes included interpersonal features, clinical care expectations, and aspects of communication. One thousand and fifty‐four eligible individuals completed the survey (88% completion rate). Most participants were middle aged (mean 48 years, SD 16.3), white (90%), and female (86%). Factor analysis showed only one relevant factor, relating to quality of PPR. The final scale ranged from possible‐96 to +96 (mean 62.0, SD 37.6). It correlated moderately with the CAT‐15 ( r =.40, P <.001) and PDRQ‐9 ( r =.30, P <.001), establishing concurrent validity. Conclusions & Inferences: We describe the development and validation of the first questionnaire for use in measuring patient expectations of the PPR, which can be used for future outcomes studies and training physicians.